Tuning of nodal line states via chemical alloying in Co2 CrX (X=Ga, Ge) Heusler compounds for a large anomalous Hall effect - Modanwal U.; Shukla G.K.; Jena A.K.; Bhattacharjee S.; D'Souza S.W.; Minár J.; Singh S. (My University, 2025)
Topological materials have attracted significant interest in condensed matter physics for their unique topological properties leading to potential technological applications. Topological nodal line semimetals, a subclass of topological materials, exhibit symmetry-protected nodal lines, where band crossings occur along closed curves in the three-dimensional Brillouin zone. When the nodal lines are gapped out due to perturbation in the Hamiltonian, a large Berry curvature (BC) arises in the surrounding area of the gapped nodal line, leading to exotic anomalous transport responses. In this paper, we studied the Co2CrX (X=Ga, Ge) Heusler compounds that exhibit mirror symmetry-protected nodal line states below the Fermi level. The BC calculation yields anomalous Hall conductivity (AHC) of about 292 and 217 S/cm for Co2CrX (X=Ga, Ge), respectively, at the Fermi level, which increases by up to 400% at the nodal line energy level. We theoretically analyzed that 20% and 60% zinc (Zn) alloying in Co2CrX (X=Ga, Ge) effectively lowers the Fermi level by 50 meV and 330 meV, respectively, aligning with the protected crossings. Consequently, we identified Co2CrGe0.4Zn0.6 and Co2CrGa0.8Zn0.2 as compositions to achieve the significant AHC of 800 and 1300 S/cm, respectively. The explicit AHC calculation for these alloyed compositions is in good agreement with our predictions. Our findings highlight that chemical alloying is an efficient way to enhance AHC in nodal line hosting materials. © 2024 American Physical Society.